2021
DOI: 10.1016/j.esmoop.2021.100153
|View full text |Cite
|
Sign up to set email alerts
|

Antineoplastic dosing in overweight and obese cancer patients: an Associazione Italiana Oncologia Medica (AIOM)/Associazione Medici Diabetologi (AMD)/Società Italiana Endocrinologia (SIE)/Società Italiana Farmacologia (SIF) multidisciplinary consensus position paper

Abstract: Most anticancer molecules are administered in body-size-based dosing schedules, bringing up unsolved issues regarding pharmacokinetic data in heavy patients. The worldwide spread of obesity has not been matched by improved methods and strategies for tailored drug dosage in this population. The weight or body surface area (BSA)-based approaches may fail to fully reflect the complexity of the anthropometric features besides obesity in cancer patients suffering from sarcopenia. Likewise, there is a lack of pharma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 121 publications
(153 reference statements)
0
23
0
2
Order By: Relevance
“…With regard to overnutrition at diagnosis and survival from childhood cancer, several potential mechanisms have been proposed. There is clinical evidence suggesting that obese patients may have altered pharmacokinetics in the metabolism of chemotherapeutic agents, although prospective trials have not confirmed such variations [ 52 , 53 ]. Overnutrition may also affect both the tumor microenvironment and the microenvironment of the host [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…With regard to overnutrition at diagnosis and survival from childhood cancer, several potential mechanisms have been proposed. There is clinical evidence suggesting that obese patients may have altered pharmacokinetics in the metabolism of chemotherapeutic agents, although prospective trials have not confirmed such variations [ 52 , 53 ]. Overnutrition may also affect both the tumor microenvironment and the microenvironment of the host [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The exploration related to refining the scheme has been carried out in different types of malignant tumors and therapeutic drugs (70,71). Cancer societies have initiated the establishment of consensus and guidelines on the dosage of drugs for specific patient populations, such as the elderly, obese and overweight patients (72,73). This disagrees with our conventional thinking, which involves the use of the body surface area and the bodyweight to calculate the dose of chemotherapy while ignoring the discrepancies noted in the response of different populations to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…56 In the context of obesity, fixed dosing can most commonly lead to underdosing, as a 1-size-fits-all approach may not accurately reflect the altered pharmacokinetics of the drug in people with obesity. 56,57 Underdosing can lead to serious lack-ofefficacy health risks.…”
Section: What Is the Role Of The Therapeutic Window Of A Drug For Inf...mentioning
confidence: 99%